Corrections to deep-rooted errors in the attribution and classification of coins of the Cilician Armenian kingdom - Vardanyan, Ruben (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
A cursory overview of the coinage of the Cilician Armenian kings clearly shows that most of the coins of the early and middle periods are of better quality and artistic design, struck with more care, and have higher weights and silver contents. These characteristics began to deteriorate over the course of the last decades of the kingdom’s existence. This general trend in the process of Cilician coin minting has been mentioned and discussed by practically all the scholars who studied this series. According to the current classification, the entire numismatic output of that kingdom is divided between fourteen kings, beginning with Levon I (1198-1219) and ending with Levon V (1374-1375), each of them being attributed certain groups of coins.